Ensuring the citizens' rights to a healthy environment: Experience of the Republic of Belarus - T.I. Makarova; V.E. Lizgaro (Ученые записки Казанского университета: Серия Гуманитарные науки)
Based on the concept of the environmental legal status of an individual, a historical and legal analysis of the experience of the Republic of Belarus in legalizing human and civil rights in the field of environmental protection was performed. Attention was drawn to the fact that ensuring and protecting the environmental citizens’ rights at the international and national levels is an important area of state environmental policy. It was shown that the environmental legal status is considered in Belarusian legal science as a system-forming category and a comprehensive institution of environmental law, in which the central element is the constitutional human right to a healthy environment, as well as citizens’ powers necessary for the implementation and protection of this right. The recognition by the Republic of Belarus of the Convention on Access to Information, Public Participation in Decision-Making and Access to Justice in Environmental Matters (Aarhus) has led to the active development of national environmental legislation in terms of securing the rights, which are needed for the right to a healthy environment. The Republic of Belarus has accumulated a constructive experience in implementing the provisions of the Aarhus Convention, but there is also a certain inconsistency in the reforms that have failed to fully contribute to ensuring the citizens’ right to a healthy environment.